Inovação e marketing: estudo de caso com empresas ganhadoras do Prêmio FINEP Inovação na categoria Produto da região Nordeste - Leitão, Patrícia Bezerra de Menezes (2005)
This work had as objective to research if the product innovation in companies of technology base at northeast region, winners of FINEP prize in product category, is consequence of market information and clients’ necessity. The intention is to mix the subjects innovations and marketing, and show that they have a relationship that can influence the development of market companies. This work uses an explorer research based in bibliographical data and documentary of primary and secondary sources, using the multiple case study method. In order to put up information about the company, it was given a structured quiz with writing and checking questions to the entrepreneurs and company managers. Two companies from Ceará and one from Paraíba were investigated. This study obtained as a result the marketing vision at the investigated companies and its relation with the innovation, or either the innovation of the awarded product came from clients’ necessity. It concludes that two of the investigated companies had a larger interaction with the appearing market, this way, the product innovation. The market research is fundamental for the creating and developing process of new products changing the market, interfering strongly in the economic development, financial and structural from companies.